(Re)Voir le Marché aux chevaux : l’éthique animalière de Rosa Bonheur - Bienvenue, Valérie (RACAR : Revue d'art canadienne / Canadian Art Review, 2022)
The Horse Fair is an iconic work by 19th century animal artist Rosa Bonheur. The immense work, which is on the scale of a history painting, has already generated numerous interpretations focusing on issues of gender and sexuality. The horses, the main subjects of the work, have been side-lined, made to serve as representations of the artist’s personality and expressions of her sexuality. My close reading of The Horse Fair reveals, by contrast, that in an era where animals were seldom accorded a voice, Bonheur sought to grant her equine subjects a measure of expressive autonomy. I consider how the work examines relational inequities between humans and horses, enabling The Horse Fair to stand as a powerful exploration of interspecies ethics.